2020
DOI: 10.1039/d0sm00738b
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–polymer triboelectricity: chemical mechanisms in the contact electrification process

Abstract: Water drops become charged after sliding on a polymer surface. The variation of the detected charge with pH and ionic strength are compatible with OH− or H+ transfer from the drop to the polymer. These changes are accounted for by a thermodynamic model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 52 publications
2
52
1
Order By: Relevance
“…On hydrocarbon (TCPS)- or fluorocarbon (PFOTS)-functionalized surfaces, drops charge positively ( Figure 2 c, green: TCPS, purple: PFOTS). 7 , 8 , 10 12 , 14 , 18 20 Hydrocarbon (TCPS) surfaces charge lower, at an initial charge of ca. 0.5 nC, which saturates to ca.…”
Section: Resultsmentioning
confidence: 99%
“…On hydrocarbon (TCPS)- or fluorocarbon (PFOTS)-functionalized surfaces, drops charge positively ( Figure 2 c, green: TCPS, purple: PFOTS). 7 , 8 , 10 12 , 14 , 18 20 Hydrocarbon (TCPS) surfaces charge lower, at an initial charge of ca. 0.5 nC, which saturates to ca.…”
Section: Resultsmentioning
confidence: 99%
“…Introduction.-Spontaneous charge-accumulation of moving drops is commonly observed in sliding (slide electrification) [1][2][3] , micropipetting [4], aerosolizing [5], bouncing [6][7][8][9][10][11] or squeezing [12] of drops. It is highly debated whether the source of this charging is electron [3,12,13] or ion transfer [14][15][16][17]. However, the electric double layer (EDL) is thought to play a key role; some of the charge from EDL is left behind on the surface as the contact line moves.…”
mentioning
confidence: 99%
“…Recently, Sosa et. al 42 showed that RH affects the charging of sliding drops only when RH >70%. Thus, we assume that relative humidity does not affect the charging process in this work.…”
Section: Discussionmentioning
confidence: 99%
“…We performed our experiments under lab ambient conditions, so we did not control RH (measured values were 30–40%). Recently, Sosa et al 42 showed that RH affects the charging of sliding drops only when RH > 70%. Thus, we assume that relative humidity does not affect the charging process in this work.…”
Section: Discussionmentioning
confidence: 99%